2002
DOI: 10.1023/a:1020238026534
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We studied the role of oxidative stress in the pathogenesis of primary pulmonary hypertension. In patients with primary pulmonary hypertension the content of malonic dialdehyde in the plasma was higher than in healthy volunteers (5.18 0.46 and 2.95 0.14 nmol/liter, respectively, p<0.01). However, glutathione peroxidase activity in the plasma decreased in these patients (0.50 0.17 vs. 1.19 0.14 U/ml in the control, p<0.05). By contrast, glutathione peroxidase activity in erythrocytes from patients surpassed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…This is in accordance with previous studies, which have shown increased oxidative stress in IPAH patients, such as increased levels of lipid peroxidation products in plasma, 7 increased DNA oxidation, 8 and decreased levels of antioxidants, α-tocopherol and β-carotene. 9 These results suggest that patients with PAH are under a higher oxidation state, therefore therapeutic strategies to inhibit ROS actions may be beneficial.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with previous studies, which have shown increased oxidative stress in IPAH patients, such as increased levels of lipid peroxidation products in plasma, 7 increased DNA oxidation, 8 and decreased levels of antioxidants, α-tocopherol and β-carotene. 9 These results suggest that patients with PAH are under a higher oxidation state, therefore therapeutic strategies to inhibit ROS actions may be beneficial.…”
Section: Discussionsupporting
confidence: 93%
“…36 Patients with pulmonary arterial hypertension (PAH) are under oxidative stress as indicated by increased lipid peroxidation, 7 increased DNA oxidation, 8 and decreased levels of tocopherols and carotenoids. 9 …”
Section: Introductionmentioning
confidence: 99%
“…For example, in patients with primary PH, GPx activity in the plasma is decreased, although erythrocytes had elevated GPx activity. This disparity was greatest in patients with severe cardiac insufficiency and PH (252). Further, patients with COPD and secondary PH have lower GPx activity in erythrocytes.…”
Section: Ros Scavenging Systems In the Pulmonary Vasculaturementioning
confidence: 99%
“…OS is commonly recognized player at the field of PAH. Signs of OS with excessive lipid peroxidation were demonstrated in PAH patients by increased levels of isoprostanes in urine [13] and malondialdehyde in plasma [32] . The other product of lipid peroxidation is hydroxynonenal (HNE).…”
Section: Introductionmentioning
confidence: 99%